2020
DOI: 10.3847/2041-8213/abaef1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding FRB 200428 in the Synchrotron Maser Shock Model: Consistency and Possible Challenge

Abstract: Recently, the discovery of Galactic FRB 200428 associated with an X-ray burst (XRB) of SGR 1935+2154 has built a bridge between FRBs and magnetar activities. In this Letter, we assume that the XRB occurs in the magnetar magnetosphere. We show that the observational properties of FRB 200428 and the associated XRB are consistent with the predictions of synchrotron maser emission at ultrarelativistic magnetized shocks, including radiation efficiency, similar energy occurrence frequency distributions, and simultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Its duration is of order ∼ milliseconds, and the luminosity and spectrum highly depends on the flare parameters. This model has been successfully applied to FRB 200428 in different details [215,216,223,224]. The observed low efficiency E radio /E X ∼ 10 −5 of FRB 200428 matches the model prediction well.…”
Section: A Far-away Model Of Metzger Et Al (2017 2019)mentioning
confidence: 60%
“…Its duration is of order ∼ milliseconds, and the luminosity and spectrum highly depends on the flare parameters. This model has been successfully applied to FRB 200428 in different details [215,216,223,224]. The observed low efficiency E radio /E X ∼ 10 −5 of FRB 200428 matches the model prediction well.…”
Section: A Far-away Model Of Metzger Et Al (2017 2019)mentioning
confidence: 60%
“…For t age ∼ 10 yr and δ 1, the RM WN is ∼ 10 5 rad m −2 . The time-dependent radio luminosity and the RM WN of FRBs with different ages can be well explained in this model (Wu et al 2020). The DM due to the nebula (Hilmarsson et al 2020) is…”
Section: Wind Environmentmentioning
confidence: 68%
“…Obviously, the merger rate of BNS or NSWD is lower than FRBs (E < 10 31 erg Hz −1 ). Based on the gravitational-wave events observed by the Advanced LIGO/Virgo gravitationalwave detectors, Zhang et al (2020) also found that only a small fraction of repeating FRBs are produced by young magnetars from BNS mergers. From the local event rate of compact binary mergers, the value of ρ BWD (0) is close to ρ FRB (0).…”
Section: Differentiation Of Various Merger Modelsmentioning
confidence: 99%
“…Another simulation showed that low-amplitude Alfvén waves from a magnetar quake can be convert to plasmoids, afterwards, collision with the wind will lead to blast waves [184]. However, this mechanism also have some defects as being disfavored recently by observations, such as the baryonic mass budget [169], the PA swing [90] and nano-second variability [112].…”
Section: Synchrotron Maser Emission From Magnetized Shocksmentioning
confidence: 99%